SIMPLE MINI AMPLIFIER - Hendro Yuhanto; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Komputer, 1999)
Simple mini amplifier is a device that has the function to strengthen the weak voicebecomes stronger. Experiment has constraints because there is an electroniccomponent that is not easily available and already there is no market.